'Are The Times A‐Changin'? Trends in adolescent substance use in Europe. (13th April 2018) - Kraus, Ludwig; Seitz, Nicki‐Nils; Piontek, Daniela; Molinaro, Sabrina; Siciliano, Valeria; Guttormsson, Ulf; Arpa, Sharon; Monshouwer, Karin; Leifman, Håkan; Vicente, Julian; Griffiths, Paul; Clancy, Luke; et al.
Abstract: Aims: To estimate temporal trends in adolescents' current cigarette, alcohol and cannabis use in Europe by gender and region, test for regional differences and evaluate regional convergence. Design and Setting: Five waves of the European School Survey Project on Alcohol and Other Drugs (ESPAD) from 28 countries between 1999 and 2015. Countries were grouped into five regions [northern (NE), southern (SE), western (WE), eastern Europe (EE) and the Balkans (BK)]. Participants: A total of 223 814 male and 211 712 female 15–16‐year‐old students. Measurements: Daily cigarette use, weekly alcohol use, monthly heavy episodic drinking (HED) and monthly cannabis use. Linear and quadratic trends were tested using multi‐level mixed‐effects logistic regression; regional differences were tested using pairwise Wald tests; mean absolute differences (MD) of predicted prevalence were used for evaluating conversion. Findings: Daily cigarette use among boys in EE showed a declining curvilinear trend, whereas in all other regions a declining linear trend was found. With the exception of BK, trends of weekly drinking decreased curvilinear in both genders in all regions. Among girls, trends in WE, EE and BK differed from trends in NE and SE. Monthly HED showed increasing curvilinear trends in all regions except in NE (both genders), WE and EE (boys each). In both genders, the trend in EE differed from the trend in SE. Trends of cannabis use increased in both genders in SE and BK; differences were found between the curvilinear trends in EE and BK. MD by substance and gender were generally somewhat stable over time. Conclusions: Despite regional differences in prevalence of substance use among European adolescents from 1999 to 2015, trends showed remarkable similarities, with strong decreasing trends in cigarette use and moderate decreasing trends in alcohol use. Trends of cannabis use only increased in southern Europe and the Balkans. Trends across all substance use indicators suggest no regional convergence.